Development of a Tuberculosis Vaccine Seed: Construction of Resuscitation-Promoting Factor B DNA Vaccine and its Expression in Vitro and in Vivo - Saraswati, Ratih D; Rukmana, Andriansjah; Fithriyah, Fithriyah; Rakhmawati, Aprilia (Makara Journal of Health Research, 2018)
Background: Tuberculosis (TB) is a chronic infection disease caused by Mycobacterium tuberculosis (Mtb) and has a high death-rate worldwide. Bacillus Calmette-Guerin is the only TB vaccine which is currently available with several drawbacks, such as its different efficacy for different individuals, lack of protection for lung TB in adults and subsequent reactivation which lead the research for novel TB vaccine approach. Resuscitation-promoting factor (rpf) protein in Mtb is a protein cluster which play a big role in TB dormancy during latent infection. Member from this cluster protein is rpfB which shows the greatest biological and immunological characteristics among other proteins in the rpf family, now is widely explored as novel TB vaccine candidate. Methods: In this study, the rpfB gene of the Mtb Beijing strain was amplified using PCR and then cloned into pcDNA3.1 plasmids. The ability of recombinant pcDNA-rpfB to induce humoral immune response was tested through Balb/C mice immunization. Results: A positive recombinant rpfB protein ~66 kDa was detected through western blot analysis using immunized mice sera. Meanwhile, recombinant pcDNA-rpfB was transfected in to CHO-K1 mammalian cell line and recombinant rpfB antigen expression was confirmed through immunostaining. Conclusions: Therefore, we have succesfully express the recombinant rpfB proten of M.tb strain Beijing in mammalian expression system which proven to be antigenically induced humoral immune response in mice model.